Problems with Physical Simulation in a Virtual Lego-based Assembly Task using Unity3D Engine - Jeffri, N.F.S. (Institute of Electrical and Electronics Engineers Inc., 2020)
Augmented Reality (AR) has potential in the manufacturing and manual assembly industry. However, the effectiveness of AR as an assistive system depends on several factors, one of which is information presentation. A set of guidelines for the effective interface design of Augmented Reality systems for manual assembly have been proposed. To validate the design guidelines, it was decided to use a simulated AR approach using Virtual Reality (VR). To evaluate the simulated AR system, it is necessary to also simulate the manual assembly task. This paper describes the challenges faced when developing the manual assembly task simulation, particularly when simulating physical interactions in VR using the Unity3D engine. Â© 2020 IEEE.